Charters and Charter Scholarship in Britain and Ireland
XI, 234 p.
Keywords: This book draws together a collection of essays looking at the ways in which charters and charter scholarship in different areas of Britain and Ireland, highlighting comparisons and contrasts in charter production and use. The book shows the crucial importance of charters as sources for understanding the history of royal administration and, more broadly, the perceptions and portrayals of kingly power, as well as developments in written culture.